KEANEKARAGAMAN JENIS TUMBUHAN PAKU-PAKUAN (PTERIDOPHYTA) DI LAHAN GAMBUT TERBUKA DI DESA SARANG BURUNG KOLAM KECAMATAN JAWAI KABUPATEN SAMBAS - Audiana, Ana; Astiani, Dwi (Universitas Tanjungpura, 2020)
Fires that often occur on peatlands in Jawai District can result in a reduction in various vegetation, one of which is fern. This study aims to obtain data on the diversity of terrestrial ferns (Pteridophyta) in open peatland in Sarang Burung Kolam Village, Jawai District, Sambas Regency. The study was conducted using a survey method with double plot sampling technique. Plots were placed on each open peat land that was burned and unburned. Laying of plots was carried out by purposive sampling in areas where many types of ferns were found. The plot area used is 5 m x 5 m divided into 25 sample sub-plots with a size of 1 m x 1 m. The results showed that in the burned and unburned land found 3 species of the same fern, Paku resam (Gleichenia linearis), Paku lemiding (Stenochlena palustris), Paku ceceran (Nephrolepis falcata). The diversity of fern species on open peatland in the Sarang Burung Kolam Village of Jawai District, Sambas Regency is relatively low.Keywords: Dominance, Diversity, Ferns, Peatlands